2007
DOI: 10.1111/j.1365-2575.2007.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Examining the integrated influence of fairness and quality on learners’ satisfaction and Web‐based learning continuance intention

Abstract: As with any other information system (IS), the success of Web-based learning depends largely on user satisfaction and other factors that eventually increase users' intentions to continue using the service (continuance intention). This research integrates the IS success model and fairness theory to construct a model for investigating the motivations behind learners' intentions to continueusing Web-based learning. Our model theorizes that the three dimensions of quality (i.e. information, system and service) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
191
2
32

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(236 citation statements)
references
References 59 publications
11
191
2
32
Order By: Relevance
“…Perceived quality affects students' satisfaction positively, which has been validated in some literatures (Chiu et al 2007;Lu and Chiou 2010;Zhao et al 2012). What concerned in this study is whether or not perceived MSNS quality will put a positive effect on satisfaction in the context of u-learning, hence, the hypothesis is put forward as follows:…”
Section: Research Model and Hypothesesmentioning
confidence: 98%
“…Perceived quality affects students' satisfaction positively, which has been validated in some literatures (Chiu et al 2007;Lu and Chiou 2010;Zhao et al 2012). What concerned in this study is whether or not perceived MSNS quality will put a positive effect on satisfaction in the context of u-learning, hence, the hypothesis is put forward as follows:…”
Section: Research Model and Hypothesesmentioning
confidence: 98%
“…In other words, system and multimedia quality seem to enhance learners' positive attitudes toward e-learning. E-learning studies that applied the information system (IS) success model found that system quality and information quality significantly influence learner satisfaction (37)(38) . Ozkan and Koseler (2009) (18) found that system quality increased the effectiveness of learning management systems while content quality created value and learner satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Using data collected from 202 learners of a Web-based learning program designed for continuing education, the results showed that utility value and satisfaction play significant roles in shaping learners' intention to continue using Web-based learning. A similar study examines the integrated influence of fairness and quality on learners' satisfaction and Web-based learning continuance intention (Chiu, Chiu, & Chang, 2007). This research theorizes that the three dimensions of quality (information, system, and service) and the three dimensions of fairness (distributive, procedural, and interactional) affect learners' satisfaction.…”
Section: Online Learning Continuance Intentionmentioning
confidence: 99%